Finite element analysis of piled raft : load transfer through piles and raft - Ibrahim Aneel Ali (2011)
Foundation system is a highly significant part of the structure and considered the most critical stage of construction of the project. It should have the obligatory capacity to carry the superstructure under different loading conditions the structure would bear throughout its lifetime. Foundation should prevent any excessive settlement and withstand any lateral force induced by the building.